RESPIRATORY DISEASES AND BRONCHOALVEOLAR LAVAGE - TAKEYAMA, Hiroyasu; IKEJIRI, Koji; YOSHIDA, Yasuhiro; OSADA, Takahisa; TAKEO, Sadanori; MAEKAWA, Soichiro (Japanese Journal of National Medical Services, 1990)
The spectrum of respiratory diseases has changed drastically in these twenty years. It seems to be the biggest change among all the clinical subjects. That is from tubercu-losis to lung cancer and immunologic respiratory disease. The most epoch-making clinical progress was made by the invention of the flexible fiberoptic bronchoscope. Bronchoalveolar lavage (BAL) was started in 1974 and since then it has been playing great roles in diagnosis, examination of pathophysiology, and pathogenetic approach of the unknown origin of pulmonary diseases. BAL method was shown in detail. BAL lymphocytes are increase in hypersensitivity pneumonia and sarcoidosis. Neutrophils increase markedly in diffuse panbronchiolitis. Various new evidences have been disclosed in bronchial asthma. We use BAL in diagnosis of pulmonary infiltrates in immunosuppressed patients and in drug induced pneumonia. We also report new evidences in ARDS, lymphangiosis carcinomatosa and so on.